Evaluating the Internet of Things Platform for CO2 Monitoring in Sugar Refineries - Cahyari, Khamdan; Ashilah, Desi Try; Cahyani, Mita Dian; Ula, Rahmatan Amartya (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
The sugar cane industry in Indonesia makes a substantial contribution to CO2 emissions, which have a negative impact on the environment and society. This study attempts to incorporate the Internet of Things (IoT) as a reliable indicator of air quality in the sugar cane industry, specifically focusing on the CO2 metric. The research aims to monitor the air quality and provide air quality information. This aligns with the eleventh Sustainable Development Goal, which emphasizes the importance of Sustainable Cities and Communities. The implementation of a smart factory concept utilizes IoT technology to actively monitor and analyze gas emissions in real-time monitoring and assessment of the air quality so that when the CO2 level exceeds the safe limit, it can provide a warning and appropriate action can be taken immediately. The system comprises a PIC microcontroller, an ESP-8266 (wi-fi) module, and a gas analyzer. These components work together to identify and alert users when gas emissions exceed pre-established thresholds. Furthermore, the system provides consumers with regular data and notifications, thereby enhancing environmental management and monitoring. The evaluation of IoT-based CO2 monitoring can raise public awareness and air quality information. Aligning with the United Nations' Sustainable Development Goals, implementing IoT technology in the sugar industry offers a practical approach to reducing emissions and promoting sustainability.